Scenarios for upgrading and distribution of compressed and liquefied biogas — Energy, environmental, and economic analysis. (20th May 2020) - Gustafsson, Marcus; Cruz, Igor; Svensson, Niclas; Karlsson, Magnus
Abstract: In the transition towards fossil-free transports, there is an increasing interest in upgraded biogas, or biomethane, as a vehicle fuel. Liquefied biogas has more than twice as high energy density as compressed biogas, which opens up the opportunity for use in heavy transports and shipping and for more efficient distribution. There are several ways to produce and distribute compressed and liquefied biogas, but very few studies comparing them and providing an overview. This paper investigates the energy balance, environmental impact and economic aspects of different technologies for upgrading, liquefaction and distribution of biogas for use as a vehicle fuel. Furthermore, liquefaction is studied as a method for efficient long-distance distribution. The results show that the differences between existing technologies for upgrading and liquefaction are small in a well-to-tank perspective, especially if the gas is transported over a long distance before use. Regarding distribution, liquefaction can pay back economically after 25–250 km compared to steel container trailers with compressed gas, and reduce the climate change impact after 10–30 km. Distribution in gas grid is better in all aspects, given that it is available and no addition of propane is required. Liquefaction can potentially expand the geographical boundaries of the market for biogas as a vehicle fuel, and cost reductions resulting from technology maturity allow cost-effective liquefaction even at small production capacities. Highlights: Scenarios for upgrading, liquefaction and distribution of biogas are compared. Energy use, environmental impact and life cycle costs are assessed. Differences between different upgrading and liquefaction technologies are small. Liquefaction makes long-distance distribution more efficient. LBG can expand the geographical area for the CBG market.